Drug Utilization Patterns in the Emergency Department of Najran University Hospital, Najran - Alkahtani, Saad Ahmed (Journal of Pharmacy Practice and Community Medicine)
Background: Study on the drug utilization pattern in emergency department (ED) is important not only for the general physician but also for the emergency physicians. It provides the means of evaluating drug prescribing trends, cost-effectiveness and efficiency of hospital formularies. Objective: The objective of this study was to evaluate the drug utilization pattern in Najran university hospital to assess drug prescribing trends, average number of drug per prescription, the WHO core indicators for drug utilization and prescription cost during patients visit at the ED. Methods: It was a retrospective cross-sectional study of all the adult patients who attended the ED at Najran university hospital. Results: The average age of the patients was 38±16 years. The average no drugs per prescription, was 2.39 ± 0.55, with a significant number of patients in this study (31%) receiving at least two drugs per episode. The majority of drugs were administrated by the oral route (68%) followed by the parenteral route (23%) and then other routes (7%). Conclusion: Antiinfective drugs cost was the highest among all the drug classes prescribed. Anti-infective were the most frequent class of drug administrated to the patients. Highest no of drugs were prescribed for respiratory tract infection followed by renal and gastrointestinal disease.
Keywords: Drug utilization; Emergency department; WHO core indicator; Prescribing trend; Antibiotic